ANALISIS PENYERAPAN TENAGA KERJA PADA INDUSTRI KECIL PERABOT RUMAH TANGGA DARI KAYU (Studi Kasus Kabupaten Klaten) - Venty Oviartha Pradana; Arif Pujiyono (Universitas Diponegoro, 2014)
ABSTRACTHome industry of household ware made of wood has a potential to decrease the number of unemployed citizens because will recruits many labor. This industry that in Klaten has increased production value. Unfortunately, this increasing was not balanced with the increasing of investment value, material, and the number of employee. The purpose of this research is to analyze the in influance of wage capital and production value to word labor demand. This research use the concept of elasticity of demand and offer of employee which based on production theory function. The research used primary data from direct interviews to 91 correspondents whom are entrepreneurs of household ware home industry at Klaten with lists of questions which have been prepared before. To reach the goal, this research use, OLS analysis method. The result of the research shows that: 1. The influence of wage towards the recruitment is negative and not significant to in fluance labor demand. 2. The influence of working capital towards recruitment is positive and significant, means the increase of material will improve the number of recruitment. 3. The influence of production value is positive and significant means the improvement of production value will increase the recruitment number.